2022
DOI: 10.3389/fimmu.2022.854848
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Associated With CD4+ T-Cell Infiltration With Gene Coexpression Network in Dermatomyositis

Abstract: BackgroundDermatomyositis is an autoimmune disease characterized by damage to the skin and muscles. CD4+ T cells are of crucial importance in the occurrence and development of dermatomyositis (DM). However, there are few bioinformatics studies on potential pathogenic genes and immune cell infiltration of DM. Therefore, this study intended to explore CD4+ T-cell infiltration–associated key genes in DM and construct a new model to predict the level of CD4+ T-cell infiltration in DM.MethodsGSE46239, GSE142807, GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“… 23 , 24 EVPL has shown association with chronic inflammation and immune responses, notably with CD4 T cell infiltration in the dermatitis studies, 25 indicating its potential role in regulating skin inflammation through immune regulation. 26 A diverse array of cytokines, growth factors, chemokines and inflammatory mediators can be secreted in the tumor microenvironment to promote tumor immunosuppression and accelerate tumor progression. 27 In this study, a correlation was observed between EVPL and the infiltration of Macrophages, Mast cells resting, and Dendritic cells resting.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 EVPL has shown association with chronic inflammation and immune responses, notably with CD4 T cell infiltration in the dermatitis studies, 25 indicating its potential role in regulating skin inflammation through immune regulation. 26 A diverse array of cytokines, growth factors, chemokines and inflammatory mediators can be secreted in the tumor microenvironment to promote tumor immunosuppression and accelerate tumor progression. 27 In this study, a correlation was observed between EVPL and the infiltration of Macrophages, Mast cells resting, and Dendritic cells resting.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA has been successfully applied to identify gene modules with various biological functions or cellular characteristics (35,36). In our study, we used WGCNA to establish a co-expression network of lncRNAs and obtained multiple modules through co-expression relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of each motif in a gene set was estimated by calculating the area under the curve (AUC) for each motif-motif pair. The NES of each motif was calculated from the AUC distribution of all motifs in the gene set [ 14 ].…”
Section: Methodsmentioning
confidence: 99%